Mbd2 enables tumourigenesis within the intestine while preventing tumour‐promoting inflammation. Issue 3 (16th May 2018) - May, Stephanie; Owen, Heather; Phesse, Toby J; Greenow, Kirsty R; Jones, Gareth‐Rhys; Blackwood, Adam; Cook, Peter C; Towers, Christopher; Gallimore, Awen M; Williams, Geraint T; Stürzl, Michael; Britzen‐Laurent, Nathalie; et al.
Abstract: Epigenetic regulation plays a key role in the link between inflammation and cancer. Here we examine Mbd2, which mediates epigenetic transcriptional silencing by binding to methylated DNA. In separate studies the Mbd2 −/− mouse has been shown (1) to be resistant to intestinal tumourigenesis and (2) to have an enhanced inflammatory/immune response, observations that are inconsistent with the links between inflammation and cancer. To clarify its role in tumourigenesis and inflammation, we used constitutive and conditional models of Mbd2 deletion to explore its epithelial and non‐epithelial roles in the intestine. Using a conditional model, we found that suppression of intestinal tumourigenesis is due primarily to the absence of Mbd2 within the epithelia. Next, we demonstrated, using the DSS colitis model, that non‐epithelial roles of Mbd2 are key in preventing the transition from acute to tumour‐promoting chronic inflammation. Combining models revealed that prior to inflammation the altered Mbd2 −/− immune response plays a role in intestinal tumour suppression. However, following inflammation the intestine converts from tumour suppressive to tumour promoting. To summarise, in the intestine the normal function of Mbd2 is exploited by cancer cells to enable tumourigenesis, while in the immune system it plays a key role in preventing tumour‐enabling inflammation. Which role is dominant depends on the inflammation status of the intestine. As environmental interactions within the intestine can alter DNA methylation patterns, we propose that Mbd2 plays a key role in determining whether these interactions are anti‐ or pro‐tumourigenic and this makes it a useful new epigenetic model for inflammation‐associated carcinogenesis. © 2018 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.